The role of intellectual property in innovation and creativity in enterprises - Khong Quoc Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Today, innovation is a widely used term in scientific research, business production activities, government management documents, and in the media, with the implication of enhancing productivity, promoting competitive advantage and commerce, thereby contributing to economic growth. This article provides another perspective on innovation, the dialectical relationship between innovation and creativity. The article also clarifies the issue of intellectual property in innovation. In this issue, innovation is the process, intellectual property is the product. Intellectual property may be the result of the innovation process, but intellectual property is also an input, an important and irreplaceable resource of the innovation process. Code: 24041201